2022
DOI: 10.1001/jamanetworkopen.2022.14688
|View full text |Cite|
|
Sign up to set email alerts
|

Categorization of Opioid Use Among Pregnant People and Association With Overdose or Death

Abstract: IMPORTANCEEarly identification of people who use opioids in pregnancy may improve health outcomes for pregnant people and infants. However, characterization of diverse circumstances surrounding type of opioid use and indications for opioid use are lacking. OBJECTIVE To develop clinically distinct groups of people who use opioids in pregnancy and to evaluate their association with drug overdose or death up to 1 year post partum. DESIGN, SETTING, AND PARTICIPANTS This is a population-based, repeated cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…These rates are high in comparison to the prevalence rates from a study conducted in 2017 which showed lower rates for tobacco (14.7%), cannabis (7.1%), and alcohol use (11.5%) among pregnant women [ 22 ]. Further, opioid use during pregnancy is associated with an increased risk for postpartum drug overdose or death [ 24 ]. Depressive disorders and substance use/abuse are often comorbid and are co-occurring risk factors for each other [ 25 ]; this comorbidity yields higher risks for suicide [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These rates are high in comparison to the prevalence rates from a study conducted in 2017 which showed lower rates for tobacco (14.7%), cannabis (7.1%), and alcohol use (11.5%) among pregnant women [ 22 ]. Further, opioid use during pregnancy is associated with an increased risk for postpartum drug overdose or death [ 24 ]. Depressive disorders and substance use/abuse are often comorbid and are co-occurring risk factors for each other [ 25 ]; this comorbidity yields higher risks for suicide [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses included (1) classifying the outcome as a developmental screening composite of physician visits for 18-month enhanced well-child visits, neurodevelopmental assessment or paediatric developmental assessment (to assess additional developmental screening); (2) classifying the exposure as NAS (to assess different follow-up care); (3) classifying the exposure according to five distinct subgroups of people who Original research used opioids in pregnancy, using a previously generated latent class analysis 33 (LCA) of 20 social, clinical and pharmacological factors (online supplemental table 4), including short-term analgesia with low comorbidity (group 1), analgesia in young people (group 2), MOUD or unregulated opioid use (group 3), pain management with comorbidity (group 4) and mixed opioid use+high social and medical needs (group 5); (4) excluding children residing in rural areas (to assess receiving well-child care from a nursing station in remote areas not captured in our data); (5) excluding children with zero well-child visits (to assess primary care not captured by our data); and (6) excluding children with birth hospitalisations of >56 days (to evaluate different care received while hospitalised).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] weeks' gestation in Ontario, Canada, between 1 January 2014 and 28 February 2018. Ontario has a universal publicly funded healthcare system.…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Categorization of Opioid Use Among Pregnant People and Association With Overdose or Death,” 1 published May 27, 2022, there was an error in the text, tables, figure, and supplement. These sections should have stated that adjusted rate ratios were calculated, not adjusted relative risks.…”
mentioning
confidence: 99%
“…These sections should have stated that adjusted rate ratios were calculated, not adjusted relative risks. This article has been corrected …”
mentioning
confidence: 99%